2005
DOI: 10.1093/intimm/dxh221
|View full text |Cite
|
Sign up to set email alerts
|

CD25+CD4+ regulatory T cells exert in vitro suppressive activity independent of CTLA-4

Abstract: Cytotoxic T lymphocyte antigen-4 (CTLA-4) is constitutively expressed on CD25(+)CD4(+) regulatory T cells (Treg) and is suggested to play a role in Treg-mediated suppression. However, the results of analysis with anti-CTLA-4 have been controversial. We addressed this issue by analyzing mice over-expressing or deficient in CTLA-4. For over-expression, CTLA-4 transgenic mice expressing a full-length (FL) or a truncated (TL) mutant of CTLA-4 were analyzed. FL T cells expressed similar levels of CTLA-4 to Treg, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 31 publications
4
51
2
1
Order By: Relevance
“…3D). These results are consistent with a previous study performed on CTLA-4 transgenic regulatory cells (30). Previous studies have also shown that regulatory cells from CTLA-4-deficient mice retain regulatory activity (30 -32).…”
Section: Effect Of Ctla-4 Overexpression On Regulatory T Cellssupporting
confidence: 93%
“…3D). These results are consistent with a previous study performed on CTLA-4 transgenic regulatory cells (30). Previous studies have also shown that regulatory cells from CTLA-4-deficient mice retain regulatory activity (30 -32).…”
Section: Effect Of Ctla-4 Overexpression On Regulatory T Cellssupporting
confidence: 93%
“…Some reports argue that anti-CTLA-4 treatment is likely to influence the action of Treg, but more recent data imply that the antitumor effects of CTLA-4 blockade are due to increased T cell activation rather than inhibition of Treg. 42,43 In our model, detailed analysis showed that CTLA-4 blockade and CD25 depletion markedly enhanced the frequency of glioma-specific effector T cells with a predominant increase in the CD81 T cell numbers. This is in line with previous observations that the frequencies of antigenspecific CD81 T cells are increased most prominently if CTLA-4 blockade is performed in CD25-depleted animals.…”
Section: Discussionmentioning
confidence: 75%
“…This finding further extends the report by DiPaolo et al [28], and suggests that control of CD80/86 expression on DCs is critical for the suppressive effects of iTreg cells. This observation is important as iTreg cell-mediated resistance of DCs to LPSinduced maturation could play a role in adjusting the intensity of antimicrobial immune responses and sustaining gastrointestinal homeostasis [29,30].The role of CTLA4 in Treg cell-mediated immune suppression remains elusive [31,32]. Our studies indicate that CTLA4 expression on iTreg cells is important for iTreg-cell function as blocking this molecule completely abolished the capacity of iTreg cells to regulate DC maturation status.…”
mentioning
confidence: 78%